MODIFIKASI & PENGEMBANGAN PERMAINAN ULAR TANGGA DALAM PENGENALAN MATERI BELAJAR PADA SISWA PAUD DI TK-HANGTUAH 3 SURABAYA - Dzulkifli, Dzulkifli; arumsari, andini dwi; Maulidiyah, Ummi Masrufah (Universitas Narotama, 2025)
This study wants to determine the effectiveness of learning both in the introduction of material in early childhood by using educational game tools through modification and development of snake and ladder games. Methods: The research used the Experimental Method involving 25 students of class A2 TK Hangtuah 3 Surabaya. Results: Based on the results of the research obtained, namely: 1) Providing knowledge to children through the learning process of playing while learning. 2) Stimulating the development of thinking, creativity, and language in order to be able to foster good attitudes, mentalities, and morals. 3) Creating an engaging play environment, providing a sense of security, and fun. 4) Know how to lose and win. 5) Learn to work together in groups and wait for your turn. Conclusion: in the development and modification of educational game tools (APE), this snake and ladder is very satisfactory from the teaching teacher and this APE is considered very effective and practical Keywords: snake and ladder game, introduction to learning materials